Memahami Sifat Shiddiq Nabi Muhammad SAW Perspektif Bisnis Syariah (Universitas Islam Negeri Sunan Kudus, 2018)
The Qur'an is very concerned about ethics in business. The people of Medina are people who often cheat in measuring and weighing, so Allah SWT decreases the surat of al-Mutaffifin as a threat to those who cheat in business. Siddiq is very closely related to business ethics. Siddiq in modern business ethics is often understood by the word “integrity”. Integrity is an essential principle in business. Integrity itself is a way of upholding the values and ethics of business. The values and ethics in doing business clearly have a big contribution in doing business. Integrity in business alone must be invested in someone who wants to run a business or is running a business. Business people must make this integrity a basic principle in their business.Siddiq (integrity, honesty) is defined as the basis of speech, beliefs and actions based on Islamic teachings. So that it can be concluded that the nature of Siddiq is still very relevant to modern business ethics, or in other languages that the nature of Siddiq is universal business ethics meaning that it does not recognize the basic values underlying the ethics.